The Passion of the Christ: A Modern Mystery Play - Madden, Ronald (Journal of religion and health, 2004)
In a review article the author reflects upon the recent film by Mel Gibson in the tradition of the medieval mystery play. As the biblical story of human origins begins in a garden, so too does this story of the birth of a new creation brought into being by the suffering of Jesus. With an understanding and acceptance of Jesus' unique vocation as the Christ, Mary is a central figure of spiritual empowerment to her son as he fulfills his mission.